Superradiance and stability of Kerr black hole enclosed by anisotropic fluid matter - Mohsen Khodadi (Elsevier, 2021)
Focusing on the rotating black hole (BH) surrounded by the anisotropic fluid matters; radiation, dust, and dark matter, we study the massive scalar superradiant scattering and the stability in the Kiselev spacetime. Superradiance behavior is dependent on the intensity parameter of the anisotropic matter K in the Kiselev spacetime. By adopting the manifest of low-frequency and low-mass for the scalar perturbation, we find K<0 enhances the superradiance scattering within the broader frequency range, compared to K=0 while K>0 suppresses within the narrower frequency range. As a result, the radiation and dark matter around the rotating BH act as amplifier and attenuator for the massive scalar superradiance, respectively. This is while the dust has a twofold role because of admitting both signs of K. Through stability analysis in the light of the BH bomb mechanism, we show in the presence of dark matter, the instability regime of standard Kerr BH (K=0) gets improved in favor of stabilization while the radiation and dust do not affect it. In other words, by taking the dark matter fluid around BH into account, we obtain a broader regime that allows the massive scalar field dynamic to enjoy superradiant stability.